1983
DOI: 10.1021/jf00120a051
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of seeds of two okra cultivars

Abstract: These findings support the hypothesis that the principal cause for the observed vigor and higher yield in fresh weight of the tobacco plants that were treated with aldicarb is its effect on the carbohydrate (increase) and protein (decrease) content of the plant. Other things being equal, the higher concentration of water-soluble sugars in the treated plants may have developed a higher osmotic pressure that increases the absorption and/or retention of water in the plant tissue. This is reflected in the whole pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 8 publications
4
19
0
Order By: Relevance
“…Overall, these data suggested two possible trends; increased processing appeared to decrease cystine and increase proline. Previously reported amino acid values for whole okra seeds (Al-Wandawi, 1983) and okra FFF (Yang et al, 1985) appear to be similar to the values reported from this investigation for whole okra seeds and okra FFF, except that glutamic acid, glycine and leucine values obtained in this study were lower than previously reported values. All five okra products were limiting in threonine, isoleucine, leucine, and valine.…”
Section: Comparative Amino Acid Profilessupporting
confidence: 89%
“…Overall, these data suggested two possible trends; increased processing appeared to decrease cystine and increase proline. Previously reported amino acid values for whole okra seeds (Al-Wandawi, 1983) and okra FFF (Yang et al, 1985) appear to be similar to the values reported from this investigation for whole okra seeds and okra FFF, except that glutamic acid, glycine and leucine values obtained in this study were lower than previously reported values. All five okra products were limiting in threonine, isoleucine, leucine, and valine.…”
Section: Comparative Amino Acid Profilessupporting
confidence: 89%
“…Protein was, however, found to be less in dehydrated okra than in fresh samples. Whole mature okra pods are rich in lysine and methionine (Al-Wandawi, 1983: Savello et al 1980. The decrease in protein content of dehydrated okra samples could be due to Maillard reaction with loss of water and carbon dioxide.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Okra seeds, like soyabean, is a rich protein source and has a high lysine level and is therefore used as a supplement to cereal-based diet that have lysine as a limiting amino acid [11]. The rare combination of seed protein rich and balanced in tryptophan, lysine and sulphur-containing amino acids (unlike cereal proteins) makes okra seeds exceptionally useful in diet.…”
Section: Introductionmentioning
confidence: 99%